Psychoanálysis and Jacques Lacan - Pita Z., Renzo (2012)
This paper aims to show part of the study by the Lacanian Psychoanalysis Group of San Marcos University, which takes as the central postulate of Lacan the unconscious is structured like language, we make a first approximation to the arguments that made possible such a statement, and show the consequences that occurred in psychoanalysis during its implementation. For this paper we made a brief explanation of the place of Jacques Lacan in psychoanalysis, then performs a development on the structure of language that is in the unconscious, to which reference is made to Ferdinand de Saussure and Roman Jakobson. Finally, we introduce some concepts as Other and Intersubjectivity in order to show the clinical approach way that follows the tenets of Lacan.